Phosphor-free InGaN micro-pyramid white light emitting diodes with multilayer graphene electrode. Issue 122 (24th November 2015) - Fu, Binglei; Cheng, Yan; Si, Zhao; Wei, Tongbo; Zeng, Xionghui; Yuan, Guodong; Liu, Zhiqiang; Lu, Hongxi; Yi, Xiaoyan; Li, Jinmin; Wang, Junxi
Abstract : We reported the combination of micro-pyramid active layers and graphene electrode to realize the phosphor-free InGaN based white light emitting diodes (LEDs). Abstract : We reported the combination of micro-pyramid active layers and graphene electrode to realize the phosphor-free InGaN based white light emitting diodes (LEDs). SEM and TEM measurements were used to characterize the structural qualities of the micro pyramid arrays. According to CL and EDX analyses, the two emitting peaks originated from the indium segregation during the MOCVD process. Multilayer graphene was used to simplify the fabrication process for the electrical connection of the micro-pyramid arrays. The wavelength shift of two emitting peaks were both small with the increase of injection currents, indicating the weak QCSE. What was more, the reverse current leakage was also quite low for the phosphor-free InGaN micro-pyramid white light emitting diodes arrays connected by graphene.